THE Pengaruh Audit Kinerja Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Kinerja Instansi Pemerintah Kabupaten Alor - Tuati, Nonce Farida; Manuain, Deetje W.; Usman, Hapsa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The purpose of this study is to analyze the influence of performance audit variables and the clarity of budget targets on the accountability of the performance of government agencies in Alor Regency, both partially and simultaneously. This study uses a quantitative approach with a descriptive method. The research population is officials involved in regional financial management, especially those responsible for the management of the APBD in the regional apparatus organization (OPD) of the Alor Regency Government. Data collection was carried out through questionnaires, which provided primary data directly from respondents. The results of this questionnaire were then analyzed using multiple regression analysis. Based on data analysis, it was found that partially, the performance audit variables and the clarity of budget targets did not have a significant influence on the accountability of the performance of government agencies. However, simultaneously, performance audits and clarity of budget targets have a significant influence on the performance accountability of government agencies. Thus, these two variables have a positive impact when applied comprehensively in the government management system. Keywords: Performance Audit, Clarity of Budget Targets, Accountability of Government Agency Performance